Sistem Informasi Perpustakaan Berbasis Web Pada Sma Negeri 1 Tegallalang - Minartiningtyas, Brigida Arie; Ariyanti, Ni Kadek Ririn (INFOTEKS (Information Technology, Computer and Sciences), 2020)
The system which is applied at the library of SMA Negeri 1 Tegallalang is still manual, where students have to search or look for the books that they need one by one. In their system, the officers will record the books borrowed by the students in a notebook. All data of the book collections in the library is also recorded in a book. For the visitor report, out book reports, book returned reports, and book data report will be recap by handwriting.This web will make the students easier to search for titles of books that they want to read or borrow. Therefore, the students no longer need to look for the title of the book they want to borrow by searching one by one on the bookcase. This system will be described in the design of Data Flow Diagrams, Conceptual Data Model, and userinterface is made for it.The results of the problem above is a library information system. This system will be able to assist students in the process of borrowing books. Moreover, it can assist the officers to record the data , reporting, bookkeeping, and the calculation of fines.